In-Vivo Test of Spirulina sp as Inducer of Î²-Actin In Cantang Grouper (Epinephelus fuscoguttatus-lanceolatus) Infected by Viral Nervous Necrosis - Irawanto, Yovan Endik; Yanuhar, Uun; Kurniawan, Andi (Faculty of Fisheries and Marine Science, Brawijaya University, Malang, Indonesia, 2018)
Cantang grouper fish (Epinephelus fuscoguttatus-lanceolatus) is a result of hybridized fish between a female of tiger grouper fish (Epinephelus fuscoguttatus) and male of kertang grouper (Ephinephelus lanceolatus). In the development of cultivation, there are many problems, one of them infected with the class of virus Nodaviridae, namely Viral Nervous Necrosis (VNN). Fish had a defense against cellular immunity against the VNN virus by Î²-actin. The aims of this research to explore the crude extract of Spirulina sp as a Î²-actin inducer for the anti-inflammatory immune system in grouper fish against VNN attack. The method used in this research is experiment methods.Â Crude extracts of Spirulina sp (33 Î¼g/ml) were conducted by feeding orally to groupers, and VNN infections were conducted by feeding the already positive VNN meat. Detection of VNN using RT-PCR, however Î²-actin detection using PCR, and IHC in the organ of Cantang grouper fish. The results showed that the percentage of DAB value of control fish (14.0%), fish treated with Spirulina sp (25.7%), fish treated with VNN (31.9%), and fish treated with Spirulina sp extract and VNN infection (32.4%). The percentage of DAB values were indicated by the detection of the target gene Î²-actin. Immunity in fish increases with the addition of Spirulina sp. The increased Î²-actin expression may also be used as an indicator of a grouper's body defense against VNN infection.